Antigenic changes among the predominantly circulating C/Sao Paulo lineage strains of influenza C virus in Yamagata, Japan, between 2015 and 2018 - Matsuzaki, Yoko; Shimotai, Yoshitaka; Kadowaki, Yoko; Sugawara, Kanetsu; Hongo, Seiji; Mizuta, Katsumi; Nishimura, Hidekazu (Infection, genetics and evolution, 2020)
Influenza C virus is a pathogen that causes acute respiratory illness in children and results in the hospitalization of infants. The antigenicity of the hemagglutinin esterase (HE) glycoprotein is highly stable, and it is not yet known whether antigenic changes contribute to the worldwide transmission and the occurrence of outbreaks of influenza C virus. Here, we performed antigenic analysis of 84 influenza C viruses isolated in Yamagata, Japan, during a 4-year period from 2015 to 2018 and analyzed sequence data for strains of the virus from Japan and many other parts of the world. Antigenic and phylogenetic analyses revealed that 83 strains belonged to the C/Sao Paulo lineage, and two sublineage strains, the Aichi99 sublineage and Victoria2012 sublineage, cocirculated between 2016 and 2018. Aichi99 sublineage strains exhibiting decreased reactivity with the monoclonal antibody YA3 became predominant after 2016, and these strains possessed the K190N mutation. Residue 190 is located in the 190-loop on the top side of the HE protein within a region that is known to show variation that does not impair the biological activity of the protein. The Aichi99 sublineage strains possessing the K190N mutation were detected after 2012 in Europe, Australia, the USA, and Asia as well as Japan. These observations suggest that antigenic variants with K190N mutations have circulated extensively around the world and caused outbreaks in Japan between 2016 and 2018. Our study indicated that the 190-loop is an important antigenic region, and the results suggested that changes in the 190-loop have contributed to the extensive transmission of the virus. •The predominant genotype of influenza C virus in Japan is the C/Sao Paulo lineage.•Two sublineages of C/Sao Paulo cocirculate in various geographic regions.•Antigenic variants with K190N mutations circulate extensively around the world.•A mutation occurring in the 190-loop is an important source of antigenic change.